Better social-emotional behavior in young Nepali children is associated with household wealth, child age, and family participation in a community development intervention - Miller, LC; Neupane, Sumanta; Shrestha, M.; Joshi, N.; Lohani, M.; Thorne-Lyman, A. (Kathmandu University, 2023)
Background: Mental health and behavior problems are under-recognized in low- and middle- income countries, especially in young children. Early identification of these problems could encourage governments to address the shortages of child mental health professionals and promote early intervention programs to help children achieve their full developmental potential.